Expression of intercellular adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1) on proliferating vascular endothelial cells in diabetic epiretinal membranes. Issue 5 (May 1994) - Tang, S; Le-Ruppert, K C; Gabel, V P
Abstract : The present study demonstrated the expression of intercellular adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1), the proliferating status of the neovascular endothelial cells, and the activation of vascular endothelial cells bearing the two cell adhesion molecules in diabetic epiretinal membranes by using double immunofluorescence and APAAP techniques. The results showed that ICAM-1 was detected in 36 out of 40 (90%) proliferative diabetic retinopathy epiretinal membranes, VCAM-1 was found in 32 out of 40 cases (80%); in 21 out of 26 (81%) vascularised membranes the endothelial cells of the new vessels in the membranes were still in a proliferative stage (positive for proliferating endothelial cell marker EN 7/44) and, further, in 20 out of 26 cases (77%) ICAM-1 was detected on the proliferating endothelial cells and VCAM-1 was found in 21 cases (81%). The expression of cell adhesion molecules, especially ICAM-1 and VCAM-1 in diabetic epiretinal membranes suggests that cell to cell interactions may play a significant role in the development of PDR membranes. In particular, the expression of ICAM-1 and VCAM-1 on proliferating endothelial cells indicates the activation of these cells, which is the first critical step for lymphocyte/endothelial cell interactions and the initiation of immune responses. The significance of proliferating status of the neovascularisation in the membranes may be related to the clinical course and prognosis of the disease.